Effectiveness Competency Based Curriculum To The Student Value Course Prodi D3 Midwifery Stikes Harapan Bangsa Purwokerto - Feti Kumala Dewi; Maya Safitri (Universitas Harapan Bangsa Purwokerto, 2016)
Competency-based education emphasizes the ability to be possessed by the graduates,Implications of competency-based education is the development of syllabi and competency-basedassessment system. Education curriculum Midwifery Studies Program D III STIKES HarapanBangsa Purwokerto consists of an academic curriculum that covers 60% of the core curriculumand 40% of the curriculum of the institution. The core curriculum reflects the Learning Outcomes(LO) and core competencies, while the institutional curriculum represents the specificity / featuredfrom courses / institutions, each of which consists of 50% and 50% of global capabilitiesinstitutional capacity. Outcomes of the educational curriculum Midwifery Studies Program aims toachieve competence D3 Studies Program. Curriculum development Midwifery Studies Program D3 STIKES Harapan Bangsa Purwokertobased on a curriculum workshop organized by the institution in two time periods: in 2010 and2011 resulted in the curriculum is competency-based curriculum, which commenced in 2012.This research is an analytic correlational. Sampling in this study using purposive sampling,sample of this research is secondary data from BAAK about Value 9 Subjects (Pregnancy,Childbirth, Postpartum, BBL, Midwifery Community, Communications, Ethics in Midwifery,Reproduction, and BEONC) and Grade Student Prodi Midwifery D3 STIKES Harapan BangsaPurwokerto academic years 2013-2014 and 2014-2015. The analysis was performed with theMann whiney, Chi Square and Kolmogorov Smirnov. The results of the study are Competency Based Curriculum (KBK) effectively against ProdiMidwifery Student Achievement Index D3 STIKES Harapan Bangsa Purwokerto with the results ofthe Mann Whitney U test p = 0.001. Competency-Based Curriculum (KBK) effectively againstValue Subjects Midwifery in the Community Midwifery Prodi D3 STIKES Harapan BangsaPurwokerto. Keywords: Competency-Based Curriculum, Values Subject, Grade Point